2015
DOI: 10.1172/jci78087
|View full text |Cite
|
Sign up to set email alerts
|

T cell signaling abnormalities contribute to aberrant immune cell function and autoimmunity

Abstract: R e v i e w S e R i e S : A u t o i m m u n i t y2 2 2 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
154
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 196 publications
(154 citation statements)
references
References 107 publications
0
154
0
Order By: Relevance
“…Thus, the early elevation of IFN-γ, followed by significant increases in BLyS and APRIL when within one year of disease classification when SLE is imminent, supports the model that simultaneous dysregulation of T helper, regulatory, IFN-related, and TNF-related pathways may unleash an inflammatory cycle that erodes immune tolerance to a point where clinical disease is inevitable [18]. Such alterations are likely due to abnormalities in receptor-mediated proximal and distal signaling pathways [68], many of which are current targets for novel therapeutic approaches to dampen inflammation and target organ damage in SLE [69]. Additional, future studies will be required to determine if dysregulation of signaling pathways that leads to aberrant cellular activation and secretion of inflammatory mediators is due to genetic [23, 70], epigenetic [71], and/or environmental triggers, such as vitamin D deficiency [51] and/or immune dysregulation caused by latent Epstein-Barr viral infection [72, 73].…”
Section: Discussionmentioning
confidence: 76%
“…Thus, the early elevation of IFN-γ, followed by significant increases in BLyS and APRIL when within one year of disease classification when SLE is imminent, supports the model that simultaneous dysregulation of T helper, regulatory, IFN-related, and TNF-related pathways may unleash an inflammatory cycle that erodes immune tolerance to a point where clinical disease is inevitable [18]. Such alterations are likely due to abnormalities in receptor-mediated proximal and distal signaling pathways [68], many of which are current targets for novel therapeutic approaches to dampen inflammation and target organ damage in SLE [69]. Additional, future studies will be required to determine if dysregulation of signaling pathways that leads to aberrant cellular activation and secretion of inflammatory mediators is due to genetic [23, 70], epigenetic [71], and/or environmental triggers, such as vitamin D deficiency [51] and/or immune dysregulation caused by latent Epstein-Barr viral infection [72, 73].…”
Section: Discussionmentioning
confidence: 76%
“…It is a key cytokine involved in the pathogenesis of autoimmune diseases including SLE [10, 33, 34]. Increased number of Th17 cells as well as high serum levels of IL-17 has been demonstrated in SLE patients [3537].…”
Section: Il-17 In Slementioning
confidence: 99%
“…Teff cells contribute to the immune response by producing pro-inflammatory cytokines, whereas Treg cells suppress immunity and inflammation. Overactive Teff cells and pro-inflammatory cytokine production have been implicated in the pathogenesis of systemic lupus erythematosus (SLE) (1). Studies in SLE patients and murine models of lupus have shown increased frequencies of Th1 and Th17 cells, as well as enhanced level of IFNγ and IL-17 (2–4).…”
Section: Introductionmentioning
confidence: 99%